Experimental and Numerical Stress Distribution of Molar Teeth with Different Type of Fillings - Bedaiwi, Bashar Owaid; Matab, Zaineb Wared (Al-Nahrain Journal for Engineering Sciences, 2017)
The human body poses the most important aim for many researchers. In nowadays, the science complex required the involvement of many resources and the coordinated team work of doctors, engineers, and other from the specialists. In the case of dental medicine, due to the nature of teeth material, their dimension and geometrical position, very important problems, like cavities that led to tooth losses. In this study, both the Experimental methods as well as the numerical finite element method have been used to analyze the stress within human teeth under forces similar to those that usually occur during chewing process with different type of food in experimental work. It was manufactured a device Resembling chewing process with vertical movement by converting circular movement into reciprocating. And used DAQ system (strain gauge sensor, DAQ and LABVIEW program) to measure the stress and strain resulted from tooth during the mastication process. Models of Natural lower first molars teeth were collected. All the teeth were cleaned from the soft tissue and stored in saline at room temperature. The teeth were randomly divided into two experimental groups according to the treated cavities shape (class I and class II) each class restored with two type of dental fillings material (Nanohybrid composite and Microhybrid composite), and then strain gauge was bonded at a buccal surface of tooth used. Their installed in acrylic jaws and applied different vertical loads. With used various morsels with different elastic modulus. The stress was calculated at the crown. In numerical 2D model of teeth were created by software Auto CAD (V.14) using wheeler ’s data were transfer to ANSYS mechanical APDL (V. 16), subjected load at model similar at that applied at the Experimental work. Class I exhibited the highest stresses compared with class II, in two case Nanohybrid bear stress higher than microhybrid composite. At class I the stress at Nanohybrid is higher than Microhybrid for all morsels by rate (12.96%, 21.48%, 41.8%, 16.56%, 16.86% and 15.74%) at (E1, E2, E3, E4, E5 and E6) respectively, and the stress at Nanohybrid is higher than Microhybrid by almost (36.67%, 45.69%, 47.89%, 34.21%, 41.2% and 165.01%) respectively at the same morsels used at class II. _x000D_ Keywords: , , .